Evaluation of centering ability of XP endo shaper, Edge Evolve and Hyflex CM in simulated curved canals - Van B. Werdina; Ihsan N. Bahnam (Erbil Dental Journal)
Background and objectives: Cleaning and shaping principles of root canal must aim to respect the continuously tapering funnel from the root apex to the coronal access cavity, follow the original canal shape and maintain the apical foramen in its original spatial relationship to the periapical tissues and root surface. This study was conducted to compare centering ability using: XP endo shaper, Edge Evolve and Hyflex CM nickeltitanium instruments in simulated curved canals.